2009
DOI: 10.1111/j.1438-8677.2008.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Urea derivatives on the move: cytokinin‐like activity and adventitious rooting enhancement depend on chemical structure

Abstract: Urea derivatives are synthetic compounds, some of which have proved to be positive regulators of cell division and differentiation. N-phenyl-N'-(2-chloro-4-pyridyl)urea (forchlorofenuron, CPPU) and N-phenyl-N'-(1,2,3-thiadiazol-5-yl)urea (thidiazuron, TDZ), well known urea cytokinin representatives, are extensively used in in vitro plant morphogenesis studies, as they show cytokinin-like activity often exceeding that of adenine compounds. In recent years, renewed interest in structure-activity relationship stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 92 publications
0
19
0
1
Order By: Relevance
“…FCF is a synthetic urea derivative with strong cytokinin activity in plants [17]. Deemed as an agent with relatively short half-life and low in vivo toxicity, FCF is a government-approved fertilizer used in fruit horticulture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FCF is a synthetic urea derivative with strong cytokinin activity in plants [17]. Deemed as an agent with relatively short half-life and low in vivo toxicity, FCF is a government-approved fertilizer used in fruit horticulture.…”
Section: Discussionmentioning
confidence: 99%
“…FCF is a synthetic plant cytokinin that consists of a chlorinated pyridine and a phenol ring joined together by a urea group [17]. FCF was fortuitously discovered to reversibly affect the localization and morphology of septins in the budding yeast Saccharomyces cerevisiae [18].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] The classical approaches to preparet hese molecules are based on the use of toxic reactants, such as phosgenea nd its derivatives or oxalyl chloride and its derivatives. [1][2][3][4][5][6][7][8][9][10][11] The classical approaches to preparet hese molecules are based on the use of toxic reactants, such as phosgenea nd its derivatives or oxalyl chloride and its derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…FCF promotes cell division and is involved in cell growth and differentiation. It has a cytokinesis inhibitor effect in higher concentrations [1]. It was incidentally found that FCF causes rapid and reversible deformation of septin filament on the bud neck in yeast [2].…”
Section: Introductionmentioning
confidence: 99%